Abdominal pregnancy with a live fetus - a case report - Edral,Ana (2020)
Abdominal pregnancy is a rare condition defined by the implantation of the embryo in the peritoneal cavity, exclusive of tubal, ovarian or intraligamentary pregnancy. It is a rare event with high maternal morbidity and mortality. The authors report the case of a secondary abdominal pregnancy with a live fetus at 10 weeks of pregnancy.